Oral Labetalol Verses Oral Nifedipinein Hypertensive Disorders of Pregnancy- A Comparative Study - Shalini Bhushan; Sunita Singhal (Asian Journal of Medical Research, 2019)
Background: Hypertensive disorders of pregnancy are the common medical disorders in pregnancy. The present study was conducted to compare oral labetalol and oral nifedipine in hypertensive disorders of pregnancy. Subjects and Methods: The present study was conducted on 60 pregnant women. Preterm or term pregnant women with severe preeclampsia/ eclampsia and BP ?160/100 mm Hg were included in the study. Patients were divided into 2 groups of 30 each. Group I patients were given oral labetamol and group II were given oral 10 mg Nifedipine. Results: Primi was seen in 18 in group I and 17 in group II, G2 6 in group I and 5 in group II, G3 4 in group I and 5 in group II and G4 2 in group and 3 in group II. The difference was non- significant (P> 0.05). In group I, SBP was 174.2 mm Hg in group I and 166.4 mm Hg in group II, DBP was 112.6 mmHg in group I and 110.8 mm Hg in group II. The difference was significant (P< 0.05). Conclusion: The study concluded that oral Nifedipine better in terms of lowering blood pressure in pregnant ladies, although the difference was non- significant.